2004
DOI: 10.1023/b:psaq.0000007561.83444.a4
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Suicides in New York State Correctional Facilities

Abstract: In an effort to identify modifiable risk factors for suicide in New York State prisons, the authors reviewed available statistical data and also examined a series of 40 psychological autopsies conducted on suicides of inmates who had received mental health services during their incarceration. Factors associated with suicide included substance abuse, history of prior suicide attempts, mental health treatment prior to incarceration, recent "bad news," recent disciplinary action, and manifestation of agitation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 0 publications
5
59
0
Order By: Relevance
“…1 Psychological research dominated these few decades of research, while sociological inquiry into prison suicide was underdeveloped (Liebling, Durie, Stiles, & Tait, 2005). One reason for this imbalance was that the bulk of the research consisted of descriptions of a small group of inmates who committed suicide while incarcerated in a particular prison for a specified time frame (Anno, 1985;Daniel & Fleming, 2006;Jones, 1986;Kovasznay, Miraglia, Beer, & Way, 2004;Salive, Smith, & Brewer, 1989;Way, Miraglia, Sawyer, Beer, & Eddy, 2005). Given the nature of the data, these studies rarely offered conclusions about the relationship between the prison environment and suicide.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…1 Psychological research dominated these few decades of research, while sociological inquiry into prison suicide was underdeveloped (Liebling, Durie, Stiles, & Tait, 2005). One reason for this imbalance was that the bulk of the research consisted of descriptions of a small group of inmates who committed suicide while incarcerated in a particular prison for a specified time frame (Anno, 1985;Daniel & Fleming, 2006;Jones, 1986;Kovasznay, Miraglia, Beer, & Way, 2004;Salive, Smith, & Brewer, 1989;Way, Miraglia, Sawyer, Beer, & Eddy, 2005). Given the nature of the data, these studies rarely offered conclusions about the relationship between the prison environment and suicide.…”
Section: Introductionmentioning
confidence: 92%
“…Studies typically relied on descriptions of a small sample of suicide cases to produce prediction profiles that ultimately proved ineffective in preventing suicide (Kennedy & Homant, 1988). More recent studies compared suicide cases with other samples of inmates who did not commit suicide or nonincarcerated populations including either suicide cases outside prison or characteristics of the United States resident population in general (Kovasznay et al, 2004;Salive et al, 1989;Way et al, 2005;White et al, 2002). By relying on suicide cases drawn from mental health treatment records, recent analyses provided no information on the suicide cases that did not have contact with prison mental health services, resulting in a possible selection bias and uncertainty as to the relationship between the mental health of inmates and suicide.…”
Section: Introductionmentioning
confidence: 99%
“…Though limited, there is an emerging body of literature that suggests agitation or overarousal is an acute risk factor for suicide (Busch and Fawcett, 2004;Busch et al, 2003;Kovasznay et al, 2004). In addition to literature directly examining the role of agitation per se, research on agitated-related constructs also provides some support for this hypothesis.…”
Section: Discussionmentioning
confidence: 90%
“…Those whose death by suicide is imminent are physiologically aroused (Busch and Fawcett, 2004;Busch et al, 2003;Hall et al, 1999); were they not, something as daunting as death would likely be too difficult to enact. Indeed, many of them are physiologically overaroused (Busch and Fawcett, 2004;Busch et al, 2003;Kovasznay et al, 2004).…”
Section: Why Would Sleep Problems Be Involved In Suicidality?mentioning
confidence: 99%
“…Consistent with these findings, reported that agitation that occurred within the week before death was a strong indication of imminent risk of suicide. Kovasznay, Miraglia, Beer, and Way (2004) also found that 70% of 40 inmates who died by suicide in a New York state prison exhibited significant agitation prior to dying by suicide. Further substantiating the relationship between agitation and imminent suicide, evaluated the clinical correlates associated with severe suicide attempts in 100 patients admitted to emergency mental health care units immediately following a suicide attempt.…”
Section: Discussionmentioning
confidence: 99%